2014
DOI: 10.1111/bju.12693
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism (VTE) prophylaxis and urological pelvic cancer surgery: a UK national audit

Abstract: ObjectivesTo evaluate the use of post-discharge venous thromboembolism (VTE) prophylaxis in UK pelvic cancer centres consistent with national guidelines. MethodsData was collected from healthcare professionals from 64 UK pelvic cancer centres. ResultsAfter radical cystectomy (RC), all cancer centres routinely use low-molecular-weight heparin (LMWH) in the perioperative period. After RC 67% of cancer centres use post-discharge LMWH routinely. After radical prostatectomy (RP), 98% of units use perioperative LMWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…It is widely becoming acknowledged that RP procedures are becoming less invasive, favouring laparoscopic and robot‐assisted approaches over conventional open techniques. In 2012, 69% of RP cases were performed either robotically or laparoscopically , with only 31% being performed open.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely becoming acknowledged that RP procedures are becoming less invasive, favouring laparoscopic and robot‐assisted approaches over conventional open techniques. In 2012, 69% of RP cases were performed either robotically or laparoscopically , with only 31% being performed open.…”
Section: Discussionmentioning
confidence: 99%
“…The Level 1 evidence supporting the use of extended thromboprophylaxis has largely been from studies of non-urologic cancer [34–36]. This combined with the variable recommendations for extended prophylaxis and provider concerns of post-operative hemorrhage might explain the lower compliance and slow uptake of extended thromboprophylaxis treatment for bladder cancer patients [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent national survey conducted in the UK among 64 pelvic cancer centres reported that, after radical cystectomy, all centres routinely use LMWH in the peri-operative period and 67% do so after discharge [6]. Similarly, for radical prostatectomy, 98% used peri-operative prophylaxis while 61% also used it after discharge.…”
Section: Variations In the Use Of Venous Thromboembolism Prophylaxis mentioning
confidence: 99%
“…When comparing the thromboprophylaxis guidelines a spectrum of recommendations appear (Table 3). This divergence of recommendations contributes significantly to the heterogeneity of practice among urologists [4][5][6].…”
Section: Trade-off Of Bleeding and Venous Thromboembolism Risk For Pamentioning
confidence: 99%
See 1 more Smart Citation